Preservice Biology Teachers’ Beliefs About Evidence-Based Medicine and Alternative Medicine - Schmidt, Elvira; Zeyer, Albert; Kremer, Kerstin; Justus Liebig University Giessen (My University, 2024)
Health-related discussions in society and the media—specifically during the COVID-19 pandemic—showed that individuals are confronted with Alternative Medicine and Evidence-Based Medicine. When making reflective decisions about these treatments, both knowledge and beliefs are important. Previous research with preservice biology teachers has shown that they commonly use Alternative Medicine, although they have little knowledge about it. To date, systematic studies on preservice biology teachers’ beliefs about Alternative Medicine and Evidence-Based Medicine are lacking. Based on the Theory of Planned Behavior, the present study elicited German (N = 40) preservice biology teachers’ beliefs about these treatments via an open-ended questionnaire. Behavioral, normative, and control beliefs were categorized using qualitative content analysis. The results showed that the participants mentioned the efficacy, scientificity, and safety of treatments as important beliefs. For Alternative Medicine, beliefs were related to scientific evidence for its efficacy, naturalness and mild effects. These beliefs indicate that some preservice biology teachers do not have a clear understanding of Evidence-Based Medicine and Alternative Medicine, which can influence their decision-making. The results highlight the need to incorporate Alternative Medicine and Evidence-Based Medicine into health-related decision-making within biology education and biology teacher education and provide a basis for further research.
Keywords: ddc:570